On the puzzling case of sodium saccharinate 1.875‐hydrate: structure description in (3+1)‐dimensional superspace. Issue 1 (23rd December 2019) - Rekis, Toms; Schönleber, Andreas; van Smaalen, Sander
Abstract : A high‐ Z ′ structure of sodium saccharinate 1.875‐hydrate has been found to be a commensurately modulated structure well described in (3+1)‐dimensional superspace. Abstract : The structure of sodium saccharinate 1.875‐hydrate is presented in three‐ and (3+1)‐dimensional space. The present model is more accurate than previously published superstructures, due to an excellent data set collected up to a high resolution of 0.89 Å −1 . The present study confirms the unusual complexity of the structure comprising a very large primitive unit cell with Z ′ = 16. A much smaller degree of correlated disorder of parts of the unit cell is found than is present in the previously published models. As a result of pseudo‐symmetry, the structure can be described in a higher‐dimensional space. The X‐ray diffraction data clearly indicate a (3+1)‐dimensional periodic structure with stronger main reflections and weaker superstructure reflections. Furthermore, the structure is established as being commensurate. The structure description in superspace results in a four times smaller unit cell with an additional base centring of the lattice, resulting in an eightfold substructure ( Z ′ = 2) of the 3D superstructure. Therefore, such a superspace approach is desirable to work out this high‐ Z ′ structure. The displacement and occupational modulation of the saccharinate anions have been studied, as well as their conformational variation along the fourth dimension.